(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Leukoplakia of the oral cavity, is one the most common potentially malignant disorder can that becomes life-threatening if not diagnosed early. Various literature has been discussed about the predisposing factor of Candida in leukoplakia. Oral leukoplakia can turn into a potentially fatal condition, and the fungus Candida albicans invasion has been associated to particular clinical traits such as tissue damage, lesion size, location in the mouth cavity, dysplastic changes, and cigarette usage. To manage this problem, a number of therapeutic approaches have been used, such as antioxidant therapy, carotene supplements, and antifungal medications. The purpose of this paper is to describe a case of Oral Leukoplakia that was complicated by Oral Candidiasis.